EROSÃO HÍDRICA SOB CONDIÇÕES DE CHUVA SIMULADA EM SOLO COM DIFERENTES TIPOS DE COBERTURA VEGETAL - Monteiro, Felipe; Falcão, Karina; Menezes, Roniedison; Serpa, Kelvin; Sotolani, Bruno; Panachuki, Eloi (ANAIS DO ENIC, 2018)
-